2021
DOI: 10.1186/s13098-021-00731-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of turmeric on lipid profile, malondialdehyde, liver echogenicity and enzymes among patients with nonalcoholic fatty liver disease: a randomized double blind clinical trial

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is one of the most common causes of liver transaminases elevation and a global health concern. Purpose This study designed to evaluate the effects of turmeric rhizomes (Curcumalonga Linn.) on liver enzymes, Lipid profiles and Malondialdehyde (MDA) in patients with NAFLD. Study design Randomized double-blind placebo controlled trial. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 61 publications
3
33
0
Order By: Relevance
“…40,42 We saw no effect of curcumin on plasma levels of GLP-1 during OGTT, contrasting to previous preclinical findings of curcumin-induced secretion of GLP-1. [58][59][60] We saw no effects of curcumin on anthropometric measures, confirming negative findings from most, 42,43,49,[61][62][63] but not all, previous human studies. [64][65][66] Obesity is associated with low-grade inflammation, which is often considered the culprit of the development of many obesity-related conditions and co-morbidities.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…40,42 We saw no effect of curcumin on plasma levels of GLP-1 during OGTT, contrasting to previous preclinical findings of curcumin-induced secretion of GLP-1. [58][59][60] We saw no effects of curcumin on anthropometric measures, confirming negative findings from most, 42,43,49,[61][62][63] but not all, previous human studies. [64][65][66] Obesity is associated with low-grade inflammation, which is often considered the culprit of the development of many obesity-related conditions and co-morbidities.…”
Section: Discussionsupporting
confidence: 83%
“…[38][39][40][41][42] Another study found a reduction in ultrasoundassessed HFC in the curcumin-treated group, but not when comparing with placebo. 43 Importantly, ultrasound is inferior to MRS [7][8][9] and considered sensitive only for HFC above 12.5%, 44 confounding the above-mentioned results. To our knowledge, the present study is the first to investigate curcumin's effect on MRS-assessed HFC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In animal stress models, curcumin has protected against increases in oxidative stress by lowing malondialdehyde and protein carbonyl concentrations, and increased the activity of antioxidant enzymes such as superoxide dismutase, catalase, and glutathione peroxidase [ 10 , 38 , 39 , 55 ]. Human trials have also confirmed curcumin’s antioxidant effects via reductions in malondialdehyde in adults with non-alcoholic fatty liver disease [ 103 ] and moderately physically active females [ 104 ]. Moreover, increased catalase activity in haemodialysis patients [ 105 ] and total antioxidant capacity and glutathione levels in adults with type 2 diabetes and coronary heart disease [ 106 ] have been observed.…”
Section: Curcumin’s Potential Antidepressant Mechanisms Of Actionmentioning
confidence: 99%